Penerapan Sistem Informasi Geografis (SIG) dalam Pemantauan Tutupan Hutan di Kabupaten Blora - Erika Puji Suhartanti (JATISI, 2025)
Monitoring changes in forest area in Blora Regency is crucial, given that Blora Regency boasts extensive forest cover. This study aims to analyze the magnitude of changes in forest area in Blora Regency from 2020 to 2024 using a Geographic Information System (GIS). The analysis shows that during this period, forest area in Blora Regency experienced a downward trend, averaging 0.01 hectares annum. GIS has proven to play a crucial role in detecting changes in forest area and in integrating and supporting decision-making in sustainable forest management.